Corona kills corona: convalescent sera option for global war against corona virus disease 2019 - ., Babita; Punia, Anita; Jha, S. K.; Jangra, Mahavir (International Journal Of Community Medicine And Public Health, 2020)
On December 31st, 2019 China reported first case of atypical pneumonia in Wuhan, the capital of Hubei province. The causative virus was found to be a beta coronavirus, closely related to the severe acute respiratory syndrome coronavirus (SARS-CoV-1) from 2003 and similar to Sarbeco viruses isolated from bats. It was therefore termed SARS-CoV-2 and the disease was named corona virus disease 2019 (COVID-19). The outbreak in Wuhan expanded quickly and led to the lockdown of Wuhan and other parts of China. While the lockdown, at least temporarily, brought the situation under control in China, but SARS-CoV-2 spread globally causing a pandemic with more than 4 lakh infections and about 19000 fatalities (as of March 25, 2020). Nucleic acid tests that detect the SARS-CoV-2 RNA genome were quickly developed and are now widely employed to diagnose COVID-19.